CircHIPK3 prevents chondrocyte apoptosis and cartilage degradation by sponging miR‐30a‐3p and promoting PON2. Issue 9 (18th June 2022) - Shang, Jie; Li, Huizi; Wu, Biao; Jiang, Ning; Wang, Bin; Wang, Dawei; Zhong, Junlong; Chen, Yufeng; Xu, Xianghe; Lu, Huading
Abstract: Osteoarthritis (OA) is a common joint disease featured by the deterioration of articular cartilage and chondrocyte death. Emerging evidence has indicated that circular RNAs (circRNAs) play an essential role in OA progress. Here, we found that the expression of circHIPK3 was significantly decreased in human and mouse OA cartilage. Knocking down circHIPK3 increased apoptosis and intracellular ROS level in HC‐a chondrocytes. We performed proteomic studies and identified that circHIPK3 regulated chondrocyte apoptosis through the mitochondrial pathway. Results of JC‐1 staining and western blot further confirmed that mitochondrial outer membrane permeabilization was promoted in HC‐a chondrocytes transfected by circHIPK3 siRNA. In terms of mechanism, we showed that PON2 functioned as a potential target of circHIPK3 to regulate chondrocyte apoptosis. Moreover, we revealed that circHIPK3 interacted with miR‐30a‐3p to regulate PON2 expression in chondrocytes. Taken together, our findings suggested that circHIPK3 regulated chondrocyte apoptosis by mitochondrial pathway, and targeting the circHIPK3/miR‐30a‐3p/PON2 axis might be a potential strategy for OA treatment. Abstract : The current study revealed the important role of circHIPK3 in regulating chondrocyte apoptosis and maintaining extracellular matrix (ECM) homeostasis. Mechanistically, circHIIPK3 might serve as a sponge of miR‐30a‐3p to regulate PON2 expression. The downregulation of circHIIPK3 resulted in the increased expression of miR‐30a‐3p and decreased expression of PON2, thus leading to mitochondrial pathway apoptosis and ECM destruction.